1D numerical study of a multistage centrifugal pump during transient operation. Issue 1 (1st September 2022) - Alerci, Aldo; Vagnoni, Elena; Nicolet, Christophe; Hugo, Nicolas; Paolone, Mario
Abstract: Hydropower plants (HPPs) are acknowledged to be fundamental assets to provide generation flexibility to power systems hosting substantial amount of stochastic renewable energy sources. Within this context, providing this flexibility enforces HPP units to cross-over transient operating conditions or to operate in off-design conditions. The evaluation of the impact that such transients have on the hydraulic machines is a fundamental step to assess the operating costs in terms of lifetime reduction of the machine structural integrity. When these assessments are performed on experimental test-rigs featuring a machine's reduced scale models, testing transient regimes may potentially trigger harmful pressure profiles along the piping system as well as resonant phenomena on the test-rig. Simulating how the several state variables evolve during the experimental tests allows for the prediction of damaging circumstances and, eventually, prevent performing experimental tests in detrimental conditions. In this regard, this paper illustrates a numerical method able to reliably reproduce the experimental test-rig behavior while preserving the consistency of the scaled similarities with respect to a specific case study HPP: the Veytaux I pumped-storage hydropower plant located in Switzerland. Moreover, in this paper, the developed 1D numerical model of the EPFL Technological Platform for Hydraulic Machines experimental test-rig is presented since some of the characteristic transient sequences of the studied HPP are simulated on this model and compared to the prototype scale 1D numerical results.